2020
DOI: 10.1109/access.2020.2993544
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Optimization Clustering Scheme for Multi-Hop Underwater Acoustic Cooperative Sensor Networks

Abstract: In this paper, we propose an improved energy optimization clustering algorithm (EOCA) for the multi-hop underwater acoustic cooperative sensor networks (UWA-CSN) due to the limited energy supply of the underwater sensor nodes. The proposed EOCA scheme considers multiple factors, such as the number of neighbor nodes, the residual energy of each node, the motion of the sensor nodes caused by the ocean currents, and the distance between the sink node and each underwater sensor node. All these factors are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…For the convenience of comparison, the proposed algorithm in this paper is called ant colony optimization clustering routing (ACOCR). Five existing popular algorithms: LEACH [18], DUCS [19], LEACH-ANT [47], CUWSN [23], and EOCA [11] were chosen as the references to validate the proposed algorithm according to the number of surviving nodes, the energy consumption of the network, and the packet loss ratio. MATLAB was used to carry out the simulation where sensor nodes were randomly placed in a 3D area of 5000 m × 5000 m × 1000 m and the coordinate of the SN was (2500, 2500, 0).…”
Section: Simulation Results and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the convenience of comparison, the proposed algorithm in this paper is called ant colony optimization clustering routing (ACOCR). Five existing popular algorithms: LEACH [18], DUCS [19], LEACH-ANT [47], CUWSN [23], and EOCA [11] were chosen as the references to validate the proposed algorithm according to the number of surviving nodes, the energy consumption of the network, and the packet loss ratio. MATLAB was used to carry out the simulation where sensor nodes were randomly placed in a 3D area of 5000 m × 5000 m × 1000 m and the coordinate of the SN was (2500, 2500, 0).…”
Section: Simulation Results and Analysesmentioning
confidence: 99%
“…In conserving energy, multi-hop data transmission in long-distance communication for UWSNs is more effective than single-hop transmission [10]. Additionally, to alleviate the problems of data collision and traffic load balance, it is important to design a reliable network topology [11]. Many studies have shown that the clustering routing algorithm is capable of saving energy, avoiding collisions, and balancing traffic load because it employs the clustering topology and uses a multi-hop mechanism during the inter-cluster data transmission [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that protocols based on clusters are viable with respect to sparing energy [1]. However, since long-distance communications will cause higher energy consumption than short-distance communications, applying multi-hop transmissions among cluster heads to convey data can further reduce the energy consumption of the network [24].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater wireless sensor networks (UWSNs) consist of many underwater wireless sensor nodes distributed within the marine environment, which support a wide variety of applications such as surveillance, navigation, data acquisition, resource exploration, and disaster prevention [1][2][3]. Each sensor node of UWSNs is equipped with an acoustic modem because it uses acoustic signals to communicate with each other [4]. These nodes are capable of forming a network without any infrastructure.…”
Section: Introductionmentioning
confidence: 99%